Preliminary Survey of Pathogens in the Asian Honey Bee (Apis cerana) in Thailand - Patcharin Phokasem; Chainarong Sinpoo; Korrawat Attasopa; Sasiprapa Krongdang; Thunyarat Chantaphanwattana; Tial C. Ling; Jeffery S. Pettis; Panuwan Chantawannakul; Veeranan Chaimanee; Terd Disayathanoowat (Life, 2023)
Widespread parasites, along with emerging threats, globalization, and climate change, have greatly affected honey bees’ health, leading to colony losses worldwide. In this study, we investigated the detection of biotic stressors (i.e., viruses, microsporidian, bacteria, and fungi) in Apis cerana by surveying the colonies across different regions of Thailand (Chiang Mai in the north, Nong Khai and Khon Kaen in the northeast, and Chumphon and Surat Thani in the south, in addition to the Samui and Pha-ngan islands). In this study, we detected ABPV, BQCV, LSV, and Nosema ceranae in A. cerana samples through RT-PCR. ABPV was only detected from the samples of Chiang Mai, whereas we found BQCV only in those from Chumphon. LSV was detected only in the samples from the Samui and Pha-ngan islands, where historically no managed bees are known. Nosema ceranae was found in all of the regions except for Nong Khai and Khon Kaen in northeastern Thailand. Paenibacillus larvae and Ascosphaera apis were not detected in any of the A. cerana samples in this survey. The phylogenetic tree analysis of the pathogens provided insights into the pathogens’ movements and their distribution ranges across different landscapes, indicating the flow of pathogens among the honey bees. Here, we describe the presence of emerging pathogens in the Asian honey bee as a valuable step in our understanding of these pathogens in terms of the decline in eastern honey bee populations.